Peluang dan Tantangan Koperasi Syariah dalam Penyaluran Pembiayaan di Era Digital - Prayusniar, Fadya; Mira, Mira; Tul Jannah, Shovia; Karsidi, Karsidi (Eco-Iqtishodi : Jurnal Ilmiah Ekonomi dan Keuangan Syariah, 2025)
Islamic cooperatives have a significant contribution in improving the economic welfare of the community through financing in line with sharia principles. In this digital era, Islamic cooperatives have a great opportunity to expand access and efficiency of financing services through the use of digital technology. Even so, this transformation process also presents several obstacles. This study aims to identify the opportunities and challenges faced by Islamic cooperatives in channeling financing in the digital era and formulate strategies that can be applied to optimize these opportunities. The method used is a literature study by reviewing various sources related to the digitalization of Islamic cooperatives from the aspects of technology, operations, and sharia compliance. The results indicate that digitalization enables the expansion of service coverage, increased efficiency, and improved competitiveness. However, challenges related to data security, increasing members' digital literacy, and regulatory adjustments still need to be addressed. The strategies presented are expected to help Islamic cooperatives utilize digital technology more effectively and continue to play a role in supporting Islamic financial inclusion in Indonesia. Keywords: Sharia Cooperatives, Financing Distribution, Cooperative Digitalization